Customer Purchase Decision Model, Supply Chain Management and Customer Satisfaction: Product Quality and Promotion Analysis - Henry Mappesona; Khilyatin Ikhsani; Hapzi Ali (International Journal of Supply Chain Management, 2020)
Abstract— Supply chain management has been widely used to deliver the products and services to end customers, which mainly effects on costumers decision. This study aims to analyze the effect of product quality on purchasing decisions partially, promotion on purchasing decisions partially, and product quality and promotion on purchasing decisions simultaneously case study Botol Sosro tea product at Giant Mall Permata Tangerang. Data collections and information are taken from populations that are the object of the research or draw samples from existing populations by using the questionnaire. The respondents who will be observed with the Slovin formula are 100 respondents. Quantitative analysis method uses multiple linear regression analysis, followed by a determination analysis (R Square), partial hypothesis testing (t-test) and simultaneous (F test) with alpha 5 percent (0.05). Analysis tool uses SPSS version 23.0 for windows. The findings showed that product quality affects purchase decision partially, promotion affects purchase decisions partially, and product quality and promotion together affect purchase decision Botol Sosro tea product at Giant Mall Permata Tangerang simultaneously.